Od odpowiedzialności za siebie do współodpowiedzialności - Zielińska, Lidia (Annales. Etyka w Życiu Gospodarczym, 2012)
In this article the author will present various links between business and ethics. The idea of responsibility, used to describe legal, economic and ethical aspects, forms the main, unifying thread. The author uses it to analyze three aspects of human activity. The first, subjective, concerns self-responsibility, where individuals are striving to satisfy their needs and to achieve happiness. The second, the encounter with the Other, embraces two meanings: responsibility for and towards the Other. The third, social, extends the idea of responsibility onto the historical community we belong to. The idea of co-responsibility is not confined to our life span but it embraces future generations as well. The author will pinpoint an important element in creating the foundations of a given community, i.e. regulations that form its basis, especially the principle of justice, encompassing the distribution of goods. Many contemporary authors underline this ethical, political and economic aspect (Rawls, communitarians, Ricoeur, Habermas). The main thesis the author would like to substantiate is as follows: in business activities the ethical conduct of the individual is not sufficient. It needs to be broadened to encompass other perspectives because contemporary societies are based on the idea of co-responsibility inhabiting many dimensions.